Konstruksi Maskulinitas Laki-Laki Melalui Komodifikasi Tubuh dalam Iklan Produk Susu L-Men Gainmass (Analisis Semiotika John Fiske) - Riza Anggara Putra (IAIN Ponorogo, 2018)
Abstract: This study focused on masculinity as part of the commodification of the male body featured in the L-Men Gainmass milk advertisement in the three version, namely,